2017
DOI: 10.1016/j.chembiol.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Takinib, a Selective TAK1 Inhibitor, Broadens the Therapeutic Efficacy of TNF-α Inhibition for Cancer and Autoimmune Disease

Abstract: Summary Tumor necrosis factor α (TNFα) has both positive and negative roles in human disease. In certain cancers, TNFα is infused locally to promote tumor regression, but dose-limiting inflammatory effects limit broader utility. In autoimmune disease, anti-TNFα antibodies control inflammation in most patients, but these benefits are offset during chronic treatment. TAK1 acts as a key mediator between survival and cell death in TNFα-mediated signaling. Here, we describe Takinib, a potent and selective TAK1 inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
121
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 65 publications
1
121
1
Order By: Relevance
“…The difference between SB202190 and DMSO provided the signal-to-background ratio of our experiment. SB202190 was chosen as a positive control, as it has been shown to significantly control fibroblast-like synoviocyte activation 87 and provided a strong assay window.…”
Section: Methodsmentioning
confidence: 99%
“…The difference between SB202190 and DMSO provided the signal-to-background ratio of our experiment. SB202190 was chosen as a positive control, as it has been shown to significantly control fibroblast-like synoviocyte activation 87 and provided a strong assay window.…”
Section: Methodsmentioning
confidence: 99%
“…At present, it is believed that there are additional transcription‐independent early cell death checkpoints regulated by phosphorylation of RIPK1 . Consistent with this possibility, genetic deletion or pharmacological inhibition of TAK1 and IKKα/β resulted in further sensitization of cell death by activating RIPK1, independently of NF‐κB activation . Subsequent biochemical analyses revealed that RIPK1 phosphorylation on Ser 321 or Ser 25 by TAK1 or IKKα/β in complex‐I prevented the RIPK1‐mediated assembly of the complex‐II/necrosome and then inhibited apoptosis/necroptosis in an NF‐κB‐independent manner .…”
Section: Introductionmentioning
confidence: 92%
“…16,17 Consistent with this possibility, genetic deletion or pharmacological inhibition of TAK1 and IKKα/β resulted in further sensitization of cell death by activating RIPK1, independently of NF-κB activation. 18,19 Subsequent biochemical analyses revealed that RIPK1 phosphorylation on Ser 321 or Ser 25 by TAK1 or IKKα/β in complex-I prevented the RIPK1-mediated assembly of the complex-II/necrosome and then inhibited apoptosis/necroptosis in an NF-κBindependent manner. 20,21 Furthermore, it has been proposed that MAPK-activated protein kinase 2 (MK2) also induces RIPK1 phosphorylation in complex-I and protects against complex-II-mediated cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in cancer cells show TAK1 inhibitors reduced phosphorylation of many downstream signaling molecules including p-IKK p-p-38, and p-c-Jun following TNF stimulation. Takinib, a novel TAK1 inhibitor, has been shown to potently inhibit TAK1 (IC50 of~9 nM) in vitro kinase assays and, unlike many other TAK1 kinase inhibitors, Takinib has an exquisite selectivity towards TAK1 over all other protein kinases in the human kinome 22 . In this study we show Takinib potently reduces pro-inflammatory phenotypes and functional responses of the TLR4 receptor in response to LPS challenge.…”
Section: Introductionmentioning
confidence: 99%